Studying the influence of plasma chemical and ozone treatment on artificially implemented microflora in model aqueous solutions - Taran, G.V.; Kudin, D.V.; Zamuriev, O.O.; Opalev, P.О.; Yaroshenko, М.О.; Korneikov, О.М.; Arefiev, V.L.; Kalashnik, M.V. (Вопросы атомной науки и техники, 2021)
The pilot studies have been conducted to determine the biocidal effects of ozone and plasma chemical treatment for 1, 2, and 3 h on the strain “Moldavian” of infectious rhinotracheitis virus, reference strain of Escherichia coli ATCC 25922, atypical mycobacteria of the species Mycobacusleum phlei and archival strain of Aspergillus flavus artificially introduced into aqueous solution. It is shown that both treatments of aqueous solution contaminated with infectious rhinotracheitis virus have virucidal properties at the level of 95…100%. It was found that bactericidal (bacteriostatic) effect of ozone treatment for Escherichia coli fluid was 100% for all the time parameters. For plasma chemical treatment, the bacteriostatic effect (23%) was shown after the treatment within 3 h. The bactericidal (bacteriostatic) effect of ozone treatment for water samples contaminated with mycobacteria of the species M. phlei was only 65% at the treatment for 3 h. There was no bacteriostatic effect for plasma chemical treatment at any exposure. When studying the fungicidal (fungistatic) properties of ozone treatment for aqueous solution contaminated with a test culture of Aspergillus flavus, fungicidal properties were established (growth retardation by 95…98%). No fungicidal or fungistatic properties were shown for plasma chemical treatment.